Influence of degree of substitution on the host-guest inclusion complex between ionic liquid substituted β-cyclodextrins with 2,4-dichlorophenol: An electrochemical, NMR and molecular docking studies - Rasdi, Fairuz Liyana Mohd; Rahim, Nurul Yani; Hasim, Fara Wahida; Prabu, Samikannu; Jumbri, Khairulazhar; Manan, Ninie Suhana Abdul; Mohamad, Sharifah (Elsevier, 2019)
A mono- and di-substituted ionic liquid-β-cyclodextrin (β-CD-ILs) were synthesized and their host-guest inclusion complex with 2, 4-dichlorophenol (2,4-DCP) were evaluated by electrochemical study. First, both β-CD-ILs which is β-CD-1-BIMOTs and β-CD-2-BIMOTs were fabricated on carbon paste electrode (CPE) for determination of 2,4-DCP. The cyclic voltammetry results indicate that both β-CD-IL/CPEs exhibit higher oxidation peak current compared to native β-CD/CPE. Both complexes possess high sensitivity, stability and reproducibility. However, as the degree of substitution of ionic liquid (IL) increases, the selectivity of β-CD-IL towards 2,4-DCP decreases. Thus, it can be deduced that the degree of substitution of IL is influencing the host-guest inclusion complex of β-CD-ILs with 2,4-DCP. © 2019 Elsevier B.V.